2015
DOI: 10.1186/s12885-015-1951-0
|View full text |Cite|
|
Sign up to set email alerts
|

CYP1B1 promotes tumorigenesis via altered expression of CDC20 and DAPK1 genes in renal cell carcinoma

Abstract: BackgroundCytochrome P450 1B1 (CYP1B1) has been shown to be up-regulated in many types of cancer including renal cell carcinoma (RCC). Several reports have shown that CYP1B1 can influence the regulation of tumor development; however, its role in RCC has not been well investigated. The aim of the present study was to determine the functional effects of CYP1B1 gene on tumorigenesis in RCC.MethodsExpression of CYP1B1 was determined in RCC cell lines, and tissue microarrays of 96 RCC and 25 normal tissues. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…lncOL1 -Suz12 target gene sets (genes upregulated in lncOL1 null cells with promoters occupied by Suz12) are associated with cell growth and proliferation, and their expression is enriched in OPCs (Figure 7J). These include Igf2 , which encodes insulinlike growth factor 2 that promotes OPC growth and proliferation (Frederick and Wood, 2004; Zhang et al, 2010), H19 , which is an imprinted lncRNA that promotes progenitor cell proliferation (Ratajczak, 2012), and Cyp1b1 , which encodes the cytochrome P450 family protein that enhances cell proliferation and tumorigenesis (Mitsui et al, 2015) (Figure 7K). These genes are highly expressed in OPCs, but strongly repressed during OL maturation (Figures S6F and S6G) (Dugas et al, 2006; Zhang et al, 2014), suggesting that their expression maintains OPCs in the precursor state.…”
Section: Resultsmentioning
confidence: 99%
“…lncOL1 -Suz12 target gene sets (genes upregulated in lncOL1 null cells with promoters occupied by Suz12) are associated with cell growth and proliferation, and their expression is enriched in OPCs (Figure 7J). These include Igf2 , which encodes insulinlike growth factor 2 that promotes OPC growth and proliferation (Frederick and Wood, 2004; Zhang et al, 2010), H19 , which is an imprinted lncRNA that promotes progenitor cell proliferation (Ratajczak, 2012), and Cyp1b1 , which encodes the cytochrome P450 family protein that enhances cell proliferation and tumorigenesis (Mitsui et al, 2015) (Figure 7K). These genes are highly expressed in OPCs, but strongly repressed during OL maturation (Figures S6F and S6G) (Dugas et al, 2006; Zhang et al, 2014), suggesting that their expression maintains OPCs in the precursor state.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an increasing number of studies have shown that CDC20 is a carcinogenic factor that is widely regulated in a variety of human malignancies, including lung cancer, kidney cancer and prostate cancer. Furthermore, CDC20 is closely related topoor prognosis of a tumor [3537].…”
Section: Disscusionmentioning
confidence: 99%
“…Melatonin also promotes cancer cell apoptosis by inducing cell cycle arrest . Another phenomenon worth noting is that CYP1B1 overexpression itself could enhance proliferation, migration, and invasion of tumor cells in prostate cancer and kidney cancer . Therefore, inferior survival in the low‐Index‐III subgroup might also be attributable to overexpression of CYP1B1 in some cancer types; further experimental studies are needed to reveal the underlying mechanism in different cancer types in this note.…”
Section: Discussionmentioning
confidence: 99%
“…30 Another phenomenon worth noting is that CYP1B1 overexpression itself could enhance proliferation, migration, and invasion of tumor cells in prostate cancer and kidney cancer. 31,32 Therefore, inferior survival in the low-Index-III subgroup might also be attributable to overexpression of CYP1B1 in some cancer types; further experimental studies are needed to reveal the underlying mechanism in different cancer types in this note. The valid associations between melatonin and risk of death have facilitated randomized controlled clinical trials (RCTs) investigating the therapeutic roles of melatonin in improving survival outcomes and tumor responses.…”
Section: Discussionmentioning
confidence: 99%